2016
DOI: 10.1371/journal.pone.0168015
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Biological Function of Keratin 26, a Novel Member of Liaoning Cashmere Goat Keratin Gene Family

Abstract: In our research, we explored the relationship between Keratin 26 and the regulation of fine hair, BMP signaling pathway, MT, FGF5, and IGF-I. The result of hybridization in situ revealed that Keratin 26 was specially expressed in cortex of skin hair follicles; the result of immunohistochemistry indicated that Keratin 26 was expressed in internal root sheath, external root sheath. Then, Real-time quantitative PCR results showed that relative expressive quantity of Keratin 26 was 1.08 or 3.3 × greater in seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…RNA-seq is usual and convenient for researchers to study different animal phenotypes due to differentially expressed genes (DEGs), because we could get enough transcriptome data from small quantities of tissue samples[ 6 , 7 ]. In previous studies of hair follicle in Cashmere goats, the scientists have already found many important factors that may affect hair follicle cycle in Wnt signal transduction pathway, fibroblast growth factor (FGF) family, bone morphogenetic protein (BMP) family, Sonichedgehog (Shh) signal transduction pathway, transforming growth factor (TGF) family, Notch signal transduction pathway and so on [ 8 , 9 , 10 ]. Some genes play an activator role while other genes play roles in these pathways as the inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq is usual and convenient for researchers to study different animal phenotypes due to differentially expressed genes (DEGs), because we could get enough transcriptome data from small quantities of tissue samples[ 6 , 7 ]. In previous studies of hair follicle in Cashmere goats, the scientists have already found many important factors that may affect hair follicle cycle in Wnt signal transduction pathway, fibroblast growth factor (FGF) family, bone morphogenetic protein (BMP) family, Sonichedgehog (Shh) signal transduction pathway, transforming growth factor (TGF) family, Notch signal transduction pathway and so on [ 8 , 9 , 10 ]. Some genes play an activator role while other genes play roles in these pathways as the inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…KRT and KRTAPs contribute nearly 90% of the cashmere yield [38][39][40], demonstrating indirectly that the composition and interactions of these proteins play an important role in cashmere quality [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…KRT and KRTAPs together make up nearly 90% of the cashmere yield [38][39][40], demonstrating indirectly that the composition and interactions of these proteins play an important role in cashmere quality [41][42][43]. KRT and KRTAP gene expression directly affect the fineness and density of cashmere as well as other characteristics [44].…”
Section: Discussionmentioning
confidence: 99%